In Vitro Antifungal Susceptibility Testing of Tea Tree Oil (TTO) 5% Compared with Nystatin against Candida sp. as Important Agent of Oral Candidiasis in HIV/AIDS Patients - Eva Lydiawati; Muhammad Yulianto Listiawan; Dwi Murtiastutik; Rahmadewi Rahmadewi; Cita Rosita Sigit Prakoeswa; Christina Avanti; Endang Wahyu Fitriani; Erwin Astha Triyono; Linda Astari; Iskandar Zulkarnain (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Oral candidiasis is the most common clinical manifestation in a person infected with HIV which has been linked with the severity of the disease. Candida albicans responsible for most oral candidiasis. The increased resistance to the available antifungal drugs can reduce the efficacy of therapy. Therefore, it will be crucial to discover novel antifungal agents. One of them is tea tree oil (TTO) or Melaleuca alternifolia which has a potent antifungal effect to inhibit the growth of Candida sp.  Purpose: To evaluate the antifungal susceptibility of TTO 5% compared with nystatin against Candida sp. taken from HIV/AIDS patients. Methods: The study assessed the antifungal effect of TTO 5% and nystatin against 33 isolates of Candida sp. that was isolated from the oral cavity of 30 HIV/AIDS patients in Dr. Soetomo General Academic Teaching Hospital Surabaya, Indonesia. Antifungal susceptibility was evaluated by the disc diffusion method. The diameter of the inhibition zone was determined as the result of this study. Result: The most strains found in this study was Candida albicans (84.8%). The mean inhibition zone of nystatin against all strains was 23.24 mm whether it was 17.55 mm for TTO 5%. The inhibition zone of both TTO 5% and nystatin in Candida non-albicans were tended to be higher than in Candida albicans. It revealed that the inhibition zone of TTO 5% significantly lower than nystatin (P = 0.00; P < 0.05).Conclusion: Therefore, the antifungal susceptibility of nystatin was significantly higher than TTO 5% against Candida albicans and non-albicans.